PENGARUH PEMANFAATAN BAHAN AJAR BERBASIS AUDIO-VISUAL (VIDEO) PADA MATA PELAJARAN SEJARAH KELAS X DI SMA NEGERI 11 PANGKEP - Pattaufi Pattaufi (Universitas Negeri Makassar, 2020)
The result of this study was to determine whether there is an influence of the use of audio-visual based teaching materials on learning outcomes of History subjects in class X students of SMA Negeri 11 Pangkep. The approach chosen in conducting this research is quantitative research while the type of research used is Experiment. Data collection using observation, tests, and documentation. This research uses descriptive analysis techniques and inferential statistical analysis. The results of this study indicate that there are significant differences. This also addresses the hypothesis H1 = There is an influence after the use of audio-visual (video) based teaching materials on learning outcomes of History Subjects in class X students of SMA Negeri 11 Pangkep